Central perforation of atretic pulmonary valve using coronary microcatheter - Saurabh Kumar Gupta; Rajnish Juneja; Anita Saxena (Wolters Kluwer Medknow Publications, 2017)
Percutaneous perforation of pulmonary valve, using 0.014" guidewires meant for coronary artery chronic total occlusion (CTO), is increasingly being performed for select cases of pulmonary atresia with intact ventricular septum (PA-IVS). Despite growing experience, procedural failures and complications are not uncommon. Even in infants treated successfully, the orifice created in the atretic pulmonary valve is eccentric. In this report, we present usefulness of coronary microcatheter in alignment of perforating coronary guidewire to the center of atretic pulmonary valve resulting in central perforation.